PEMBELAJARAN DALAM JARINGAN (DARING) DI MASA PANDEMI COVID-19 SISWA MI MA’ARIF NU NGADIREJO KALIGESING PURWOREJO - nganah, isti; Nafi'ah, Siti Anisatun (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2021)
The Online Learning During Pancemic Covid-19 At MI Ma’arif NU Ngadirejo Kaligesing Purworejo Central of Java, the research of study is (1) to describe the online learning during pandemic covid-19 at MI Ma’arif NU Ngadirejo Kaligesing Purworejo (2) the supporting and inhibiting factors of online learning during pandemic covid-19 at MI Ma’arif NU Ngadirejo Kaligesing Purworejo. This reseach employs qualitative approach, the data get by the observation, documentation, and interview. The subject of research is theachers, parents and students of MI Ma’arif NU Ngadirejo Kaligesing. The analyze of data is triangulation of data with qualitative approach. The result of reseach is implementation online learning during pandemic at MI Ma’arif NU Ngadirejo Kaligesing Purworejo less effective because of several inhibiting factors, and not all of students have smartphones and the internet network is less stable.